2010
DOI: 10.1080/10253860903562155
|View full text |Cite
|
Sign up to set email alerts
|

Transnational organization and symbolic production: Creating and managing a global brand

Abstract: In recent years, there has been sustained debate pertaining to how global markets should be conceptualized, enacted, and addressed. The purpose of this study was to expose the pivotal managerial thought processes and practices of senior managers at Guinness and the actions of symbolic workers involved in the reconciliation of trends towards increasing global cultural convergence and a need for local cultural differentiation within the 'global culture industry.' Our findings reveal the strategic processes and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Future research would benefit from a more explicit investigation of the role rhetorical history may play in the context of globalization. For example, firms often struggle to position themselves effectively in industries and markets that are embedded in a variety of conflicting cultural historical constructions (e.g., domestic and global; see Amis and Silk, ): How do they assemble these into coherent toolkits of historical narratives that enable effective use of rhetorical history? How do they do such rhetorical history work?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research would benefit from a more explicit investigation of the role rhetorical history may play in the context of globalization. For example, firms often struggle to position themselves effectively in industries and markets that are embedded in a variety of conflicting cultural historical constructions (e.g., domestic and global; see Amis and Silk, ): How do they assemble these into coherent toolkits of historical narratives that enable effective use of rhetorical history? How do they do such rhetorical history work?…”
Section: Discussionmentioning
confidence: 99%
“…Extant research has tended to conceptualize organizational fields, industries, and geographically proximal communities as forming and maintaining a socially constructed system of local norms, values, beliefs, and definitions (Wooten and Hoffman, ) used to ascertain legitimacy. However, legitimacy judgments might be made within not only a local framework, but also a global one (e.g., Khaire and Wadhwani, ; Vaara and Faÿ, ), prompting actors to negotiate both local and global institutional norms (Marquis and Battilana, ; Robertson and White, ), as they seek to reconcile the dual pressures for conformity and distinctiveness (Amis and Silk, ; Kostova et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Featherstone's emphasis on the role of cultural intermediaries in mediating production and consumption has been widely accepted and applied by a range of scholarly accounts on a variety of cultural workers including, but not limited to, fashion designers (Skov 2002), business managers and accountants (Negus 2002), bookshop workers (Wright 2005), public relations practitioners (Curtin and Gaither 2005;Hodges 2006), fashion buyers (Entwistle 2006), personal fitness trainers (Smith Maguire 2008), branding consultants (Moor 2008), journalists (Doane 2009;Ma 2006), arts administrators (Durrer and Miles 2009), television buyers (Kuipers 2012), marketing/advertising practitioners (Amis and Silk 2010;Cronin 2004;du Gay et al 1997;Gee and Jackson 2012;John and Jackson 2011;Kelly et al 2005;Kobayashi 2012aKobayashi , 2012bMcFall 2002;Moor 2012;Nixon 2003;Jackson 2008, 2010;Soar 2000Soar , 2002, wine promoters (Smith Maguire 2013), specialist advisors (Rojek 2014) and more recently diary-keepers (Perry et al 2015).…”
Section: Consumptionmentioning
confidence: 99%
“…Cronin (2004) extended this assertion by adding that the "recursive relationship between practitioners' dual status as producers (of ads) and consumers (of ads and products) reproduces social division s and hierarchies" (353). Following this, Amis and Silk (2010) explored transnational organization of marketing campaigns and found the "infrastructure capable of facilitating the engagement with consumers at multiple levels across different markets" (175) through which cultural intermediaries negotiated the idiosyncrasies of local culture and consumption practice.…”
Section: Consumptionmentioning
confidence: 99%
“…Many marketing studies have revealed how collective consumers co-create the symbolic meaning of consumption (e.g. Amis and Silk, 2010;Cova and Pace, 2006;Leigh et al, 2006;Muñiz and O'Guinn, 2001;Muñiz and Schau, 2005). For example a recent study by Schau et al (2009) explored collective value creation within several brand communities and provided a comprehensive review of brand value creation processes.…”
Section: Co-creation Of Valuementioning
confidence: 99%